ENGLISH ZONE (EZO): A FUN ACTIVITY IN LEARNING ENGLISH SPEAKING SKILL FOR YOUNG LEARNERS - Linda Septiyana; puri widiarti; tika purnama sari; eka nur kasih; hijjriah al mukaromah (Universitas Perjuangan Tasikmalaya, 2020)
This research aims to describe the implementation of English Zone (EZo) activities in learning English speaking skills for young learners. Employing qualitative descriptive study, this research included observation of teaching and learning process, and interview that was administered to 10 students from Kampung Sawah, West Hadimulyo. Ten meetings were observed thoroughly. Each observation took place in English language classroom every Sunday at Al-Fatimah Mosque. This research presented the implementation of English Zone (EZo) to young learners and students’ responses to the implementation of EZo. The findings illuminated the powerful ways in which EZo was able to improve students’ speaking skill. The students were having fun in the classroom which made them actively participate IN speaking practice with their friends or teachers. The findings further highlighted that EZo showed a good result in improving students’ confidence during their speaking practice. EZo helped them to speak more and decreased hesitation. They felt more relaxed to speak.Keywords : English zone, speaking skill, young learners, activity